Seroprevalence of Human Immunodeficiency Virus Infection and Demographic Correlates among Individuals Tested in Al-Jabal Al-Akhdar, Eastern Libya: A Cross-Sectional Laboratory-Based Study (Razi Medical Journal, 2025)
HIV infection continues to represent a significant public health concern globally, particularly in regions with limited surveillance infrastructure. In Libya, the prevalence of HIV remains low but poorly characterized, and underreporting due to social stigma and regional disparities in testing complicates epidemiological assessments. Age is a key determinant of HIV risk, yet few studies have evaluated age-specific seroprevalence among Libyan nationals. This study aimed to assess HIV seropositivity and its demographic correlates, with a particular focus on age, gender, and location among Libyan nationals tested in Al-Bayda and Massa in Eastern Libya during 2025. A cross-sectional, laboratory-based study was conducted from January to October 2025. Blood samples from 195 Libyan nationals were analyzed using rapid diagnostic tests for HIV antibodies, following manufacturer guidelines and national testing algorithms. Demographic data, including age, gender, and location, were extracted from laboratory records. Statistical analysis was performed in R software, including descriptive statistics and Fisher’s exact test for categorical variables. The association between age and HIV serostatus was examined using the Wilcoxon rank-sum test, and age distribution by serostatus was visualized with a box plot. Of the 195 participants, 120 (61.5%) were male, and 75 (38.5%) were female. The mean age was 35.8 ± 15.1 years (range: 6–89 years). One individual (0.5%) tested positive for HIV, a 34-year-old male. The Wilcoxon rank-sum test comparing age distributions between HIV-positive and HIV-negative individuals indicated no statistically significant difference (W = 61, p = 0.528). Most participants were adults aged 25–45 years, aligning with globally recognized high-risk age groups. HIV seroprevalence among Libyan nationals in Eastern Libya remains very low, with minimal age-related differences observed. However, the findings emphasize the need for continued laboratory-based surveillance, targeted testing, and demographic-focused public health strategies to monitor potential shifts in age-related HIV risk.
Keywords: HIV, Libya, Age, Seroprevalence, Gender, Epidemiology, Cross-sectional Study